Resonance in Biological Systems: An Interdisciplinary View - Erich Ebner (Contemporary Perspective on Science, Technology and Research Vol. 3, 2024)
This chapter point out the fundamentals of physics and chemistry and to present them in order to promote an interdisciplinary understanding in biology and medicine on the basis of theoretical growth in knowledge. New findings can clarify existing strategies, broaden and deepen the benefits, as has been shown in wide areas of biological and medical science. And to do this you have to acquire the knowledge of basic research to an appropriate extent. Resonance is a fundamental phenomenon of the energetic processes between energy and matter. It thus combines organic matter and its function into a viable dynamic that means life. This applies to all forms of life: human, animal and plant organisms. The various detections of resonance in physical and quantum mechanical basic research make the difficulty of understanding clear. Nevertheless, an understanding of the interdisciplinary use must be developed. The pharmacological and medical-technical development of the present makes this necessary. The medical therapeutic applications and especially the physical therapy strategies in terms of the tolerability of resonant processes must be consciously recognized and observed.